Biomimetics: On the Origins of Fracture Toughness in Advanced Teleosts: How the Swordfish Sword's Bone Structure and Composition Allow for Slashing under Water to Kill or Stun Prey (Adv. Sci. 12/2019). Issue 12 (19th June 2019) - Schmidt, Felix N.; Zimmermann, Elizabeth A.; Walsh, Flynn; Plumeyer, Christine; Schaible, Eric; Fiedler, Imke A. K.; Milovanovic, Petar; Rößle, Manfred; Amling, Michael; Blanchet, Clément; Gludovatz, Bernd; Ritchie, Robert O.; et al.
Abstract : In article number1900287, Björn Busse and co‐workers investigate the osseous sword of the swordfish with respect to composition and resulting mechanical parameters. Lacking mechanosensitive osteocytes that are known to initiate repair and renewal of aged bone in other species, the sword of the swordfish exhibits a lengthwise compositional ageing pattern associated with bone toughness. Thus, the swordfish presents an intriguing model to study anosteocytic mechanisms of bone quality maintenance.